Access to Essential Medicine Issues and The Doha Declaration: contents, the legal status and the problems with implementation - Utomo, Tomi Suryo (Indonesian Journal of International Law, 2007)
The idea of the Doha Declaration was background by the protest of the developing countries who think the TRIPS Safeguards is not clear and not multi interpretation. The developing countries are trying to find a interpretation instrument to the TRIPS Safeguards that fulfill the requirements of international law, especially the Vienna Convention which set the Treaty Law and the negotiation legislative process based on the WTO decision making framework. In Doha Declaration, the developing countries reach the main purpose to find the explanation to the TRIPS Safeguards interpretation. Even in the future, the difference of the economic level, technology, and the interests of the developing countries will be the one to trigger the debate of the patent medicine protection based on the WTO provision and the influence on the essential medicine access. The best results from the debate will highly dependant to the will of the parties to find the solution which that is not taking sides to one of the state party of the WTO.